New feminist criticism: art, identity, action - Frueh, Joanna; Langer, Cassandra; Raven, Arlene; Frueh, Joanna; Langer, Cassandra; Raven, Arlene (IconEditions, 1994)
This anthology of fifteen timely articles offers a wide range of feminist criticism sparked by ideas and events of the 1980's and 1990's. The articles consider culture, language, race, identity, sexuality, gender, creativity, aging and other issues. Though different in methodology, the writings are united by their common interest in feminism as a vehicule for intellectual exploration and individual communication and understanding. In their revisionary approaches, the contributors offer exciting new insights into the complex interaction between women and cultures, questionning inclusion as well as exclusion. "New Feminist Criticism" presents the unfinished and ongoing agenda of feminism in art, society and culture.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; art contemporain; art féministe; arts; corps; cours; critique d'art; discipline; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; intersectionnalité; premier cycle; périodes historiques; race; thématiques; vieillesse

Creating worlds for my music to exist: How women composers of electroacoustic music make place for their voices - McCartney, Andra (Université York, 1994)
For this study, I have interviewed fourteen women composers of electroacoustic music in or near the three Canadian urban centres of Montreal, Toronto, and Vancouver. Montreal: Ciaire Pich6, Lucie Jasmin, Pascale Trudel, Monique Jean, Helen Hall and Kathy Kennedy; Toronto: Gayle Young, Sarah Peebles, Wende Bartley, Elma Miller, Ann Southam, and Carol Ann Weaver; Vancouver: Hildegard Westerkamp and Susan Frykberg. These interviews were all conducted between January and November of 1993. References to the development of electroacoustic music in Canada are sparse in the existing literature, both in general histories of electroacoustic music, and in histories of Canadian music. And even though there seem to be some areas of change (for instance, recent publications in Quebec), women composers are under-represented in writings and recorded collections of electroacoustic music in Canada. Chapter Two situates the work of women composers in the Canadian scene, discussing particularly the work of Norma Beecroft, Marcelle Desch§nes, Diana McIntosh, and Micheline Coulombe Saint-Marcoux. Chapter Three describes the metaphors, images and myths invoked in malestream discourses associated with electroacoustic music, in popular magazines, course texts and software. I investigate how my consultants’ language reflects and/or contests mainstream imagery, or how it might be framed by entirely different assumptions and experiences. Chapter Four is concerned with the institutional structures of electroacoustic music. I discuss how gendering exhibits itself in the division of labour in electroacoustic studio courses at universities, as well as in concert halls, conferences, and professional organizations. Excerpts from the interviews record my consultants experiences in these institutions, as students, teachers, and composers. In Chapter Five, I point out the variety of strategies that each composer uses to construct her identity within the world of electroacoustics. Each entry takes the form of a three or four page sketch, with quotes from the interview regarding the social environment, equipment choices, compositional styles, and particular pieces that my consultant discusses. Chapter Six discusses three pieces in detail: one by Susan Frykberg, Woman and House; one by Wende Bartley, A Silence Full of Sound; and one by Hildegard Westerkamp, Breathing Room. I focus on how each of the composers chooses to work with technology, and how her culturally-constructed position as a woman affects her work. I describe how my consultants imagine other stories to tell, and other possible lived social relations. The conclusions in Chapter Seven, in addition to suggesting areas for future research, discuss three themes that run throughout the study: the idea of gender as performance, the doubleness of my consultants' responses to technology, and the importance of the linguistic and musical metaphors that they use.
Keywords: 1900-1999; 1990-1999; DIG; amériques; arts; canada; discipline; femmes* artistes; genre; montréal; musique; mémoires/thèses; périodes historiques; ressource en ligne; régions géographiques; toronto; vancouver

Féminisme, art et histoire de l'art - Tucker, Marcia; École nationale supérieure des beaux-arts (France) (Espaces de l'art, 1994)
Ces cinq contributions d'historiennes de l'art et de femmes agissant dans le monde de l'art posent la question des apports du féminisme à l'art récent et au renouvellement de l'histoire de l'art, discipline largement régie, jusqu'au début des années 70, par le regard des hommes. Le féminisme a contribué à renouveler notre conception de l'art. Les auteurs de ce recueil comptent parmi les figures majeures de ce débat.
Keywords: 1900-1999; 1970-1979; 1980-1989; art occidental; arts; cours; discipline; har4600; har4610; histoire de l'art; premier cycle; périodes historiques

Mrs Dalloway - Woolf, Virginia (Collection Folio classique, 1994)
Dans son quatrième roman, Mrs Dalloway (1925), l'écrivaine anglaise Virginia Woolf aborde le sujet des classes moyennes anglaises au lendemain de la guerre de 1914-18. Elle a noté dans son journal qu'elle voulait « donner la vie et la mort, la santé mentale et la folie ; Je veux critiquer le système social, & le montrer à l'œuvre, à son plus intense'. La forme, ainsi que le contenu du roman est essentiellement "moderne". La technique pionnière du "flux de conscience" de Woolf reflétait son désir de montrer la nature multiforme de la conscience et de capturer l'impact du monde moderne en évolution rapide sur la psyché. Un récit onirique transporte le lecteur à travers une ville surpeuplée et dans l'esprit de différents individus isolés : nous nous concentrons particulièrement sur Mme Clarissa Dalloway, une dame de la société d'âge moyen et Septimus Warren Smith, un jeune soldat démobilisé en état de choc. Comme dans Ulysses (1922) de James Joyce , l'action se limite principalement à une journée ; dans ce cas en juin 1923. Le roman commence par la phrase "Mme Dalloway a dit qu'elle achèterait les fleurs elle-même" alors qu'elle passe la journée à préparer une fête, et se termine par la fête qui se déroule le soir, alors qu'elle apprend au passage le suicide de Septimus. Néanmoins, le livre nous sort de tout cadre temporel strict en incorporant des moments de réminiscence d'un certain nombre de personnages. Du passé de Septimus, nous apprenons que sa classe sociale l'a empêché d'aller à l'université ; il était « l'un de ces hommes semi-éduqués et autodidactes dont toute l'éducation est apprise dans des livres empruntés aux bibliothèques publiques », et son désir d'être poète l'a finalement conduit à s'enrôler dans l'armée, comme pour défendre un shakespearien idéalisé. Angleterre. Le traitement par Woolf des soins psychiatriques qu'il reçoit - Septimus se tue lorsqu'il apprend qu'il est interné dans un sanatorium - semble s'appuyer sur sa propre expérience de la maladie mentale. Les regrets plus doux de la classe supérieure et le sentiment d'isolement de Mme Dalloway fournissent une sorte de contre-rythme. Sa fille, Elizabeth, est inévitablement le symbole de la jeune femme de Clarissa, et elle se souvient des chemins amoureux et de la vie qu'elle n'a pas empruntés par son ancien prétendant Peter Walsh et par Sally Seton, qu'elle a embrassé une fois, mais qu'elle a maintenant épousé. un homme d'affaires provincial. Le roman est devenu l'une des œuvres les plus célèbres de Woolf et l'un des textes déterminants du modernisme littéraire.
Keywords: 1900-1999; 1910-1919; 1920-1929; arts; cours; discipline; europe; fem5050; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques; écriture des femmes*; études littéraires